Fatigue properties of a high-strength-steel welded joint - Burzić, Zijah (Materiali in tehnologije, 2007)
In addition to the strength and toughness properties, the fatigue properties of welded joints are necessary for the design of high-strength steel structures exposed to variable loading. Wöhler curves were determined for smooth tensile specimens tested with variable loading. The fatigue behaviour of a welded joint can be improved by removing the overfill; however, the fatigue properties are still lower than the values for the parent metal. Tests with pre-cracked specimens have shown the difference in the fatigue-crack growth-rate properties to be less significant than other crack parameters.
Keywords: visokotrdna jekla; zvarjeni spoji; utrujenost materialov; preiskava materiala; razpoke